Intelligent Power Quality Enhancement Strategies for PV-Integrated Smart Distribution Networks: A State-of-the-Art Review - Mir Manjur Elahi; Prakash Kumar Ray; Pratap Sekhar Puhan (International Journal of Electrical Power and Machine Systems, 2026)
The rapid integration of photovoltaic (PV) systems into modern power distribution networks has introduced significant challenges related to power quality. Issues such as voltage fluctuations, harmonic distortion, flicker, and reactive power imbalance arise due to the intermittent and nonlinear nature of solar energy generation. This paper presents a concise literature review of various power quality enhancement techniques employed in PV-integrated networks. Key approaches include the use of active power filters (APFs), dynamic voltage restorers (DVRs), unified power quality conditioners (UPQCs), and advanced control strategies such as fuzzy logic, artificial neural networks (ANN), and model predictive control (MPC). Additionally, grid-connected inverter control techniques and energy storage integration are discussed as effective solutions for mitigating disturbances. The review highlights the comparative performance of these techniques in improving voltage stability, reducing total harmonic distortion (THD), and ensuring reliable grid operation. The findings indicate that hybrid and intelligent control-based approaches offer superior performance in dynamic and uncertain conditions. Power quality issues in PV systems may now be detected and compensated for in real time thanks to recent advancements in smart grid technology and Internet of Things (IoT)-based monitoring systems. The efficiency, dependability, and fault management capabilities of the system have all been enhanced by the use of adaptive and data-driven optimization techniques. This study provides insights into the current trends and future directions for enhancing power quality in PV- based power systems.
Keywords: Active power filter; Harmonic distortion; Photovoltaic systems; Smart grid; UPQC; power quality; renewable energy integration; voltage stability